2021
DOI: 10.1108/ijoa-11-2020-2501
|View full text |Cite
|
Sign up to set email alerts
|

A literature review exploring the role of technology in business survival during the Covid-19 lockdowns

Abstract: Purpose The Covid-19 pandemic has affected every aspect of human life. Even though the pandemic length was not too long, a huge volume of research relating to Covid-19 has been published in different contexts. This paper aims to review the literature investigating the impact of Covid −19 on businesses generally and explore studies examining the technology role of business survival during the Covid-19 lockdowns specifically. Design/methodology/approach This study implemented the concept of a systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 65 publications
1
23
0
2
Order By: Relevance
“…The results of this study at the same time strengthen the results of previous research conducted by Salam et al (2021) regarding the effect of the COVID-19 pandemic on the use of social media as one of digital marketing; Abed (2021) regarding the condition of the COVID-19 pandemic being able to increase the use of technology in product marketing, including the use of digital marketing in his business; and El Chaarani et al ( 2021), found that during the COVID-19 pandemic the adoption of marketing innovations had a positive impact on business performance. These results are also strengthened by the results of research by Minai et al (2021); Jiang and Wen (2021); Kimuli et al (2021), found that the COVID-19 pandemic had a positive and significant impact on strategic digital entrepreneurship including digital marketing and encouraged the speed of adopting digital technology.…”
Section: The Effect Of the Covid-19 Pandemic On Digital Marketing Adoptionsupporting
confidence: 87%
“…The results of this study at the same time strengthen the results of previous research conducted by Salam et al (2021) regarding the effect of the COVID-19 pandemic on the use of social media as one of digital marketing; Abed (2021) regarding the condition of the COVID-19 pandemic being able to increase the use of technology in product marketing, including the use of digital marketing in his business; and El Chaarani et al ( 2021), found that during the COVID-19 pandemic the adoption of marketing innovations had a positive impact on business performance. These results are also strengthened by the results of research by Minai et al (2021); Jiang and Wen (2021); Kimuli et al (2021), found that the COVID-19 pandemic had a positive and significant impact on strategic digital entrepreneurship including digital marketing and encouraged the speed of adopting digital technology.…”
Section: The Effect Of the Covid-19 Pandemic On Digital Marketing Adoptionsupporting
confidence: 87%
“…The cost of reinstating a business to pre-pandemic operations may not only be costly, impractical, but also unsustainable (Faeste & Hemerling, 2016). In response to the pandemic, organizations have turned to online technology and digital infrastructure to make up for travel, production and connectivity to dispersed markets (Abed, 2021). This suggests that business in Africa needs to come up with creative digital technology to reboot their operations to survive.…”
Section: Resultsmentioning
confidence: 99%
“…Mobilitas manusia menjadi menurun. Hal ini berdampak pada melemahnya berbagai sektor bisnis (Abed, 2021).…”
Section: Pendahuluanunclassified